The Political History of Indagru VDC - Ollieuz, Annelies (New Angle: Nepal Journal of Social Science and Public Policy, 2011)
This paper traces how the government policies on land rights have evolved over recent decades in Nepal and analyses the roles of existing power relations and vested interests in shaping their development and implementation. It is shown that historically entrenched power relations existing in the patrimonial political system have led to a highly unequal distribution of land. Ways to reduce inequality in land ownership to provide access to land for real farmers are essential, but due to these same entrenched power relations, they have not been implemented in earnest and land reforms over the last few decades have been unsuccessful. As a result, the same types of pre-capitalist social relations have persisted in rural areas. These relations have not been able to generate an agrarian surplus that can be invested in agriculture or other sectors of the economy. Furthermore, the concept of ‘property rights’ in relation to land has created a new problem in agrarian development in recent years, by fostering an environment in which people invest in land not to increase production but for speculation. As a result, it has become extremely difficult for poor people to purchase land to have a housing lot or for farming. The present democratic politics and institutions in the post 2006 context have still not shown any capacity or the interest to address the issue of land. Accordingly, the prospects for change at the moment seem bleak even though the rhetoric has increased. Moreover, the changed context calls for a new concept of land reform. This would take into account changes in the agrarian structure and an agrarian economy where mobility is high and injection of cash from outside the country has increased. It is finally argued that successful land reform should be led by grassroots political movements, with limited external intervention.